El seguro de declaraciones y garantías en transacciones de fusiones y adquisiciones - Abad Seminario, Victor (2022)
Mergers and acquisitions transactions allow the intervening parties to create a specific legal regime applicable only to them, which distributes the responsibility for the goods transferred through the sale (whether shares, assets, or a combination of the latter that results in a running business). Within the framework of these legal regimes, an opportunity to reduce risks has been found in the insurance market, through the contracting of insurance policies that cover scenarios of responsibility of the sellers, in the event of falsehood, inaccuracy or non-compliance with the representations and warranties that they grant to buyers, and that result in damages to the latter or to the target company. In this article we address the complexity of this legal figure that even though it is not offered directly in the Peruvian market, it has been gaining strength in the region.